A struggle for definition: online narratives of Italian trans women. Issue 5 (3rd July 2020) - Primo, David; Zamperini, Adriano; Testoni, Ines
ABSTRACT: In recent years, literature in the field of trans studies suggested that there has been a widespread trend in academic debates about gender transitivity to produce monolithic conceptualizations of transness unable to account for the different gender experiences of trans individuals. This paper aims to provide a further contribution to debates in this area through an empirical investigation of trans narratives of identity and embodiment. Drawing on queer and transfeminist scholarship which framed social media as offering trans people a site for the re-negotiation of the meanings attached to gender transitivity, we conducted an abductive thematic qualitative analysis of 37 blog posts written by 10 Italian trans women concerning their experience of transness. Our findings suggest that in these posts, the bloggers realized a complex bricolage of scientific language, autobiographical storytelling and political statements which produced distinct narratives of gender transitivity. In particular, these accounts of transness diverge across different trajectories related to the negotiation of the medical discourse of gender diversity, to the articulation of the body as a site of empowerment and to how the bloggers defined which experiences of gender diversity should be included in the trans umbrella.